Notes on the Brazilian 2006 Presidential Elections: The Winding Road to Democratic Consolidation - Lucio Renno (Universidad de Los Andes, 2006)
The paper describes the main characteristics of the 2006 Brazilian Presidential elections. It explores two defining traits of this elections: the interplay between how retrospective economic voting and views towards corruption affected vote volatility and the final result of the election. The paper concludes by pointing out implications of the current elections to the strengthening of democracy in Brazil.